Building an Inclusive Economic Ecosystem: Integration of Bumdes and Msme Programs in North Lombok - Muhammad Mahfuz (Business Management, 2026)
This research aims to analyze the integration model of Village-Owned Enterprises (BUMDes) and Micro, Small and Medium Enterprises (MSMEs/UMKM) in building an inclusive economic ecosystem in North Lombok Regency. The research uses a qualitative approach with a case study design in three villages with active BUMDes: Jenggala Village, Santong Village, and Batu Tojah Village. Analysis used Miles and Huberman’s interactive model with data triangulation. Results show that: (1) BUMDes plays a strategic role in strengthening MSMEs through capital facilitation, marketing support, and human resource capacity building; (2) three effective integration models have emerged: the direct partnership model, the product clustering model, and the village digital economy model; and (3) key enabling factors include transparent governance, community participation, and regional government support, while main obstacles are limited human resources and suboptimal financial information systems.